The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1136/sti.2010.042895
|View full text |Cite
|
Sign up to set email alerts
|

Circumcision among men who have sex with men in Scotland: limited potential for HIV prevention

Abstract: ObjectiveMale circumcision has been shown to reduce the risk of HIV acquisition among heterosexual men but the impact among men who have sex with men (MSM) is not known. In this paper, we explore the feasibility of research into circumcision for HIV prevention among MSM in Scotland.MethodsAnonymous, self-complete questionnaires and Orasure oral fluid collection kits were distributed to men visiting the commercial gay scenes in Glasgow and Edinburgh.Results1508 men completed questionnaires (70.5% response rate)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The oral fluid specimen response rate was relatively low, and may not be representative. However, the overall survey response rate was higher (66% in 2005 and 71% in 2008), and there were few differences between the men who did and did not provide oral fluid specimens;7 8 suggesting that the men who provided these were representative of the larger venue-based sample. It should also be noted that the question used to derive recent HIV testing, and therefore the period defined as recent testing, was different in 2005 and 2008 (16 months in 2005 and 12 months in 2008).…”
Section: Discussionmentioning
confidence: 95%
“…The oral fluid specimen response rate was relatively low, and may not be representative. However, the overall survey response rate was higher (66% in 2005 and 71% in 2008), and there were few differences between the men who did and did not provide oral fluid specimens;7 8 suggesting that the men who provided these were representative of the larger venue-based sample. It should also be noted that the question used to derive recent HIV testing, and therefore the period defined as recent testing, was different in 2005 and 2008 (16 months in 2005 and 12 months in 2008).…”
Section: Discussionmentioning
confidence: 95%
“…In Scotland, only 14% of MSM indicated their willingness to take part in a circumcision trial [117]. One study in China found 43% of MSM were willing to be circumcised [96], and in another, 8% were willing initially, but this rose to 31% after an information session [118].…”
Section: Discussionmentioning
confidence: 99%
“…Willingness is generally low (∼10%) in high-resource settings [23], [24], but higher (∼30%) in some resource-limited Asian settings [25][27]. One San Francisco study found moderate willingness (20%) among the target population (HIV-negative, predominantly insertive, uncircumcised MSM who have UAI); however, the proportion of the MSM sample found in the target population was so small (3.7% or n = 15) that the study anticipated limited public health benefits for MSM-MC [28].…”
Section: Introductionmentioning
confidence: 99%